Va rog!!!!Pas cu pas !!!!!
Anexe:
Răspunsuri la întrebare
Răspuns de
3
[tex](8^2)^3=8^6=(2^3)^6=2^{18}\\
4^4=(2^2)^4=2^8\\
16^6=(2^4)^6=2^{24}\\
2^{18}\cdot 2^8:2^{24}=2^{18+8-24}=2^2=4[/tex]
Răspuns de
0
Salut!
(8²)³ • 4⁴ : 16^6=
2^18•2^8:2^24=
2^18+8-24=
2^2=
4
Sper că te-am ajutat !
Succes!
(8²)³ • 4⁴ : 16^6=
2^18•2^8:2^24=
2^18+8-24=
2^2=
4
Sper că te-am ajutat !
Succes!
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă